Z-source inverters with enhanced voltage boost for renewable energy systems - Li, Ding (2012)
Worldwide economic growth has initiated a strong demand for energy, which unfortunately cannot be met indefinitely by fossil fuels. That motivates the development of renewable energy systems like wind, solar and tidal farms, which by nature are non-polluting and abundant. Outputs from these renewable sources are also mostly electrical, which by far is the most efficient form of energy for transmission and distribution over long distance. Renewable energy is therefore a promising green alternative even though it is unlikely to replace fossil fuels any sooner.